Sulfur concentrations and isotope ratios in sediments from Kiel Bay, western Baltic Sea - Martin Hartmann; Heimo Nielsen (PANGAEA, 1968)
The isotope-ratios of sulfur-components in several sedimentologically different cores of recent marine sediments from Kiel Bay (Baltic Sea) were investigated. In addition, quantitative determinations were made on total sulfur, sulfate, sulfide, chloride, organic carbon, iron and watercontent in the sediment or in the pore-water solution. The investigations gave the following results: 1. The sulfur in the sediment (about 0.3 -2 % of the dry sample) was for the most part introduced into the sediment after sedimentation. This confirms the results of Kaplan et al. (1963, doi:10.1016/0016-7037(63)90074-7). The yield of Sulfur from organic material is very small (in our samples about 5-10% of the total sulfur in the sediment). 2. The sulfur bound in the sediment is taken from the sulfate of the interstitial water. During normal sedimentation, the exchange of sulfate by diffusion significant for changes in the sulfur-content goes down to a sediment depth of 4-6 cm. In this way the sulfate consumed by reduction and formation of sulfide or pyrite is mostly replaced. The uppermost layer of the sediment is an partly open system for the sulfur. The diagenesis of the sulfur is allochemical. 3. The isotope-values of the sediment-sulfur are largely influenced by the sulfur coming into the sediment by diffusion and being bound by bacteriological reduction. Due to the prevailing reduction of 32S and reverse-diffusion of sulfate into the open sea-water, an 32S enrichment takes place in the uppermost layer of the sediment. delta34S-values in the sediment range between -15 and -35 extperthousand while seawater-sulfate has +20 extperthousand. No relationship could be established between sedimentological or chemical changes and isotope-ratios. In the cores, successive sandy and clayly layers showed no change in the delta-values. The sedimentation rate, however, seems to influence isotope-ratios. In one core with low sedimentationrates the delta34S-values varied between -29 and -33 extperthousand, while cores with higher sedimentationrates showed values between -17 and -24 extperthousand. 4. As sediment depth increases, the pore-water sulfate shows decreasing concentrations (in a depth of 30-40 cm we found between 20 and 70 % of the seawater-values), and increasing delta 34S-values (in one case reaching more than +60 extperthousand). The concentration of sulfide in the pore-water increases with sediment-depth (reaching 80 mg S/l in one case). The (delta34S-values of the pore-water-sulfide in all cores show increases paralleling the sulfate sulfur, with a nearly constant delta-distance of 50-60 extperthousand in all cores. This seems to confirm the genetic relationship between the two components.
Supplement to: Hartmann, M; Nielsen, H (1968): Delta-34S-Werte in rezenten Meeressedimenten und ihre Deutung am Beispiel einiger Sedimentprofile aus der westlichen Ostsee. Geologische Rundschau, 58(2), 621-655, https://doi.org/10.1007/BF01820726